Makna BookTube bagi Para Pembaca Buku di Era Digital - Andalusia Neneng Permatasari; Izni Nur Indrawati Maulani; Kelik Nursetiyo Widiyanto; Kiki Zakiah Darmawan (CHANNEL: Jurnal Komunikasi, 2020)
The rapid development of information communication technology has led to the full utilization of digital. Online media are replacing conventional print media, digital books are starting to be looked at by publishers, and book reviews usually in regular media were transformed into the form of audiovisual called BookTube. This study aims to find out, understand, and explain how book readers and viewers of BookTube shows interpret the meaning of BookTube. The method used is a qualitative research method with a phenomenological approach. The results of this study are the construction of meaning built for the BookTube. First, BookTube is a complement to written reviews because they still feel the BookTube cannot present the essence of a book reviewer. Second, BookTube as a substitute for written book reviews because changes occur so fast, like it or not, BookTube can be used as a substitute for a new form of a book review.